2019
DOI: 10.1136/thoraxjnl-2018-212964
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate chains contribute to the anticoagulant milieu in malignant pleural effusion

Abstract: BackgroundWhile malignant pleural effusion (MPE) is a common and significant cause of morbidity in patients with cancer, current treatment options are limited. Human heparanase, involved in angiogenesis and metastasis, cleaves heparan sulfate (HS) side chains on the cell surface.AimsTo explore the coagulation milieu in MPE and infectious pleural effusion (IPE) focusing on the involvement of heparanase.MethodsSamples of 30 patients with MPE and 44 patients with IPE were evaluated in comparison to those of 33 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…This heparanase inhibitor not only reduced the heparanase level but also attenuated the levels of TF, TFPI, and TFPI-2 in the pleura and microcirculation adjacent to the pleural cavity. 19 Interestingly, in the tissues derived from mice treated with the JAK-2 inhibitor, the degree of coagulation protein staining was even lower compared with control findings. This result may imply that JAK-2 pathway activation affects the constitutional levels of these proteins in the perivascular/ intravascular space.…”
Section: Discussionmentioning
confidence: 90%
“…This heparanase inhibitor not only reduced the heparanase level but also attenuated the levels of TF, TFPI, and TFPI-2 in the pleura and microcirculation adjacent to the pleural cavity. 19 Interestingly, in the tissues derived from mice treated with the JAK-2 inhibitor, the degree of coagulation protein staining was even lower compared with control findings. This result may imply that JAK-2 pathway activation affects the constitutional levels of these proteins in the perivascular/ intravascular space.…”
Section: Discussionmentioning
confidence: 90%
“…Our recent study revealed that while the levels of coagulation system activation markers were elevated in pleural effusions of transudate, infectious pleural effusion, and malignant pleural effusion, the net effect of these effusions was anticoagulant. 58 In samples obtained from 30 patients with malignant pleural effusion, 44 with infectious pleural effusion, and 33 patients with transudate pleural effusions, levels of heparanase, factor Xa, and thrombin were significantly higher in the exudate than in the transudate. Thromboelastography showed hardly any thrombus formation in the whole blood, mainly upon the addition of malignant pleural effusion.…”
Section: Heparanase and Heparan Sulfate Chains In The Pleural Cavitymentioning
confidence: 92%
“…Accordingly, inhibition of heparanase might provide a therapeutic option for patients with recurrent malignant pleural effusion. 58…”
Section: Heparanase and Heparan Sulfate Chains In The Pleural Cavitymentioning
confidence: 99%
“…24 Hardak et al suggested that human heparinase could facilitate the anticoagulant microenvironment in MPE and cause the pleural fluid recurrence. 25 Nosti et al also clarified how Colony Stimulating Factor 1 (CSF1) augmented vascular permeability and destabilized tumour vessels to regenerate MPE. 26 In addition, Wang et al suggested a Forkhead Box P3 (FOXP3)+ natural killer T-like cell could suppress the immune microenvironment in recurrent MPE.…”
Section: Introductionmentioning
confidence: 99%
“…Hardak et al. suggested that human heparinase could facilitate the anticoagulant microenvironment in MPE and cause the pleural fluid recurrence 25 . Nosti et al.…”
Section: Introductionmentioning
confidence: 99%